2010
DOI: 10.1109/tuffc.2010.1533
|View full text |Cite
|
Sign up to set email alerts
|

A modified prandtl-ishlinskii model for modeling asymmetric hysteresis of piezoelectric actuators

Abstract: Piezoelectric actuators can offer high resolution of displacement and this makes them suitable for precise driving tasks. However, most piezoelectric actuators are made of piezoceramics which have a major drawback related to their natural hysteresis nonlinearity. To compensate the hysteresis nonlinearity of piezoelectric actuators, many hysteresis models have been proposed such as the Preisach model, the classical Prandtl-Ishlinskii model, and so on. This paper provides a new approach to model the asymmetric h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(70 citation statements)
references
References 22 publications
0
70
0
Order By: Relevance
“…5, pp. 1200-1210, May 2010 P. Li, F. Yan, C. Ge, X. Wang, L. Xu, J. Guo, and P. Li, "A simple fuzzy system for modelling of both rate-independent and rate-dependent hysteresis in piezoelectric actuators, " Mechanical Systems and Signal Processing, vol. 36, pp.…”
Section: Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…5, pp. 1200-1210, May 2010 P. Li, F. Yan, C. Ge, X. Wang, L. Xu, J. Guo, and P. Li, "A simple fuzzy system for modelling of both rate-independent and rate-dependent hysteresis in piezoelectric actuators, " Mechanical Systems and Signal Processing, vol. 36, pp.…”
Section: Referencesmentioning
confidence: 99%
“…A survey on these models can be found in [22]. Furthermore, the experimentation showed that the hysteresisnon-linearity in PEA is not symmetric and many models was proposed in [23]- [25] to describe the asymmetric hysteresis existing in PEA. To compensate the hysteresis behavior of PEA, many intelligent techniques was used such as fuzzy logic [26], [27], neural networks [28], [29], adaptive filter [30], [31], hybrid models [32], NARMAX models [33], [34] and iterative learning control [35].…”
Section: Introductionmentioning
confidence: 99%
“…The research topics include modeling of static piezoelectric hysteresis, modeling of dynamic hysteresis, feedback and feed-forward control of hysteresis, and self-sensing technique in feedback control of piezoelectric hysteresis. Several models of piezoelectric hysteresis, including the model based on hyperbola functions, the modified PrandtlIshilinskii model, and the model based on neural network have been proposed [28][29][30]. In this section, the new modified Prandtl-Ishlinskii model is introduced.…”
Section: Nonlinear Hysteresis Controlmentioning
confidence: 99%
“…The proposed asymmetric play operator [29] consists of two parts, which are called the right-side play operator (RSPO) and the left-side play operator (LSPO). They respectively represent the right-side hysteretic nonlinearity and the leftside hysteretic nonlinearity of a system with hysteresis.…”
Section: The Modified Prandtl-ishlinskii Modelmentioning
confidence: 99%
“…A modified Prandtl-Ishlinskii model was proposed by Jiang et al (2010) based on two asymmetric hysteresis operators.…”
Section: Prandtl-ishlinskii Modelmentioning
confidence: 99%